Application of Small Group Discussion Method for Improving Students' Critical Thinking Ability in Integral Material - Faoziyah, Nina; Dalimarta, Fahmy Ferdian; Kusaeri, Didi (JUPE : Jurnal Pendidikan Mandala, 2024)
The purpose of this study is to analyze the implementation of the Small Group Discussion learning method in improving students' critical thinking skills on the topic of integrals. This study employs a Classroom Action Research (CAR) design, conducted through four iterative stages: planning, action, observation, and reflection. The research subjects are students of Politeknik Muhammadiyah Tegal, focusing on enhancing their critical thinking skills using the Small Group Discussion method. Data were collected using various instruments, including pre-tests, learning outcome tests, interviews, and observations. The results indicate that the average learning score in Cycle 1 fell into the "moderate" category, with an average score of 60.26%. In Cycle 2, the results improved to the "high" category, with an average score of 78.21%. In Cycle 3, the average score significantly increased to 85.90%, which is classified as "very high." Therefore, the implementation of the learning process in Cycle 3 was deemed highly successful.